Multibody Dynamics Analysis for the Belt Drive System of the Centrifuge in Space Station - Li Tengfei; Liu Bingshan; Xue Jing; Wang Ke (Jixie chuandong)
The belt drive system can transfer power and motion by flexible body smoothly and reduce vibration. The belt drive system of the centrifuge as the core component for variable gravity experiment in space station is analyzed by multibody system dynamics. The virtual prototype is built by the belt discretization. The curves of displacement,velocity,acceleration,tension,contact are obtained by simulation. The research of dynamic characteristics of belt drive system can offer help for design and optimize.